CROSS-CULTURAL REALITIES IN THE JOURNALISTIC DISCOURSE AND THEIR SIGNIFICANCE IN FOREIGN LANGUAGE LEARNING - Natalia Glinka; Galyna Usyk; Yuliya Ilchuk (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2016)
The paper examines the journalistic discourse as a linguistic phenomenon in the socio-cultural realities. The relevance of the study is determined by the great interest of linguistic science to the issues of cross-cultural communication and their significance in teaching English as a foreign language. The journalistic discourse is a peculiar phenomenon of linguistics because it reflects socio-cultural features of specific communication space; it creates a language picture of the world of a certain culture and society through the specific socio-cultural lexical units - realities. The main aim of the study is to examine, analyze, summarize and systematize socio-cultural linguistic resources as a means of creating and transmitting linguistic awareness, revealing the pragmatic aspects of their functioning in the journalistic discourse. In order to achieve this goal the following steps have been taken: 1) to study the characteristics of the journalistic discourse; 2) to determine the specific genres of the journalistic discourse of the English language periodicals and mass media on-line resources; 3) to investigate the cognitive and pragmatic features of the vocabulary functioning, which reflect the peculiarities of the English language context of the socio-cultural aspect of the journalistic discourse; 4) to categorize and analyze the thematic and typological groups of socio-cultural realities and study their functions in the context. The possible application of the obtained results is to develop the scientific and teaching facilities in the field of foreign language learning and translation.